Functional nanoparticles obtained from cellulose: engineering the shape and size of 6-carboxycellulose - Sharma, Priyanka R.; Varma, Anjanikumar (Chemical Communications, 2013)
Agricultural residue derived cellulose and cotton cellulose were used to synthesize quasi-spherical nanoparticles of 6-carboxycellulose having diameter 25-35 nm. This provides a new range of functionalized nanostructured celluloses with increased versatility and applications. The nanoparticles were efficient in stabilizing carbon nanotube dispersions and were effective anti-microbial agents against E. coli.

Functionalized celluloses and their nanoparticles: morphology, thermal properties, and solubility studies - Sharma, Priyanka R.; Varma, Anjanikumar (Carbohydrate Polymers, 2014)
Agricultural residues derived cellulose was used to synthesize a new series of carboxy functionalized cellulosic nanoparticles (quasi-spherical shaped, 13.2-21.5% carboxyl content) and macro-sized 6-carboxycelluloses (long-fibril shaped, 1.7-22% carboxyl content). The DP (50-70) and yield (upto 46%) of nanoparticles were manipulated by controlling the reaction temperature and time. TGA/DTG thermographs of the carboxycelluloses gave thermostability data and co-related well with the residual crystalline, amorphous, and anhydroglucuronic acid content. The particle shape and size had no effect on the thermal stability. Some derivatives were fully or partially soluble in aqueous alkali and non-aqueous solvents, which can lead to increased versatility of these polymers. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: 6-Carboxycellulose; cellulose; DTG; Morphology; Nanoparticles; TGA

Supramolecular transitions in native cellulose-I during progressive oxidation reaction leading to quasi-spherical nanoparticles of 6-carboxycellulose - Sharma, Priyanka R.; Rajamohanan, Pattuparambil R.; Varma, Anjanikumar (Carbohydrate Polymers, 2014)
Cellulose-I swells considerably in phosphoric acid, and converts to amorphous cellulose via a cellulose-II transition state. Controlled oxidation of cellulose-I to 6-carboxycellulose (6CC) using HNO3-H3PO4-NaNO2 oxidation system led to the selective production of 6CC's of varying carboxyl contents (1.7-22%) as well as various shapes and sizes (macro-sized fibrils of several micron length and/or spherical nanoparticles of 25-35 nm), depending on the reaction conditions. 6CC's having less than 14% carboxyl content were largely in cellulose-II form (WAXRD values in-between cellulose I and cellulose II), whereas at 14-22% the 6CC's were largely amorphous; only trace crystallinity was observed at 19% and 22% carboxyl 6CC. Spherical nanoparticles retained a high degree of crystallinity having cellulose-I structure, whereas the macro-sized fibrils were largely converted to cellulose-II structure. Analysis by WAXRD as well as by CP-MAS C-13 NMR studies gave similar conclusions. Reduced molecular weight with progressive oxidation, including presence of oligomers, was also evident from an increase in the reducing-end carbon peak at similar to 92 ppm. For high oxidation levels (>14%) the NMR 92-96 ppm peaks disappeared on extracting with dilute alkali, due to soluble oligomers being removed. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Carboxycellulose; cellulose; Nanoparticles; NMR; WAXRD

Thermal stability of cellulose and their nanoparticles: Effect of incremental increases in carboxyl and aldehyde groups - Sharma, Priyanka R.; Varma, Anjanikumar (Carbohydrate Polymers, 2014)
Oxidized cellulose containing carboxyl and aldehyde functional groups represent an important class of cellulose derivatives. In this study effect of incrementally increasing COOH and CHO groups at C2, C3, and C6 positions of cellulose and nanocellulose has been investigated, with a view to understanding their effect on thermal treatment of cellulose. The results show that 2,3-dialdehyde cellulose (DAC) is the most thermally stable oxidized product of cellulose while the most unstable derivatives contain carboxyl group at the C6 position (6CC). Carboxymethylcellulose (CMC), with carboxymethyl group on C6 position, is more stable than 6CC. Multi-functionalized celluloses 2,3,6-tricarboxycellulose and 6-carboxy-2,3-dialdehyde, have the same level of thermal stability as 6CC, showing that the presence of carboxyl at the C6 is a key destabilizing factor in the thermal stability of oxidized cellulose products. More the number of reducing end groups on the polymer chain, lower the thermal stability of the cellulose, as proved by comparing the TGA/DTG of monomeric analogs dextrose, cellobiose and glucuronic acid with the oxidized celluloses. The thermal stability trend observed for oxidized celluloses was DAC > DCC > nanoparticles > dextrose >glucuronic acid, caused by extent of reducing ends and COOH groups. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: 2; 3; 3-Dialdehyde cellulose; 6-Carboxycellulose; 6-Tricarboxycellulose; cellulose; TGA/DTG

Shape and size engineered cellulosic nanomaterials as broad spectrum anti-microbial compounds - Sharma, Priyanka R.; Kamble, Sunil; Sarkar, Dhiman; Anand, Amitesh; Varma, Anjanikumar (International Journal of Biological Macromolecules, 2016)
Oxidized celluloses have been used for decades as antimicrobial wound gauzes and surgical cotton. We now report the successful synthesis of a next generation narrow size range (25-35 nm) spherical shaped nanoparticles of 2,3,6-tricarboxycellulose based on cellulose I structural features, for applications as new antimicrobial materials. This study adds to our previous study of 6-carboxycellulose. A wide range of bacteria such as Escherichia coli, Staphloccocus aureus, Bacillus subtilis and Mycobacterium tuberculosis (non-pathogenic as well as pathogenic strains) were affected by these polymers in in vitro studies. Activity against Mycobacteria were noted at high concentrations (MIC99 values 250-1000 mu g/ml, as compared to anti-TB drug Isoniazid 0.3 mu g/ml). However, the broad spectrum activity of oxidized celluloses and their nanoparticles against a wide range of bacteria, including Mycobacteria, show that these materials are promising new biocompatible and biodegradable drug delivery vehicles wherein they can play the dual role of being a drug encapsulant as well as a broad spectrum anti-microbial and anti-TB drug. (C) 2016 Published by Elsevier B.V.
Keywords: Anti-microbial; cellulose; Spherical nanoparticles; Tricarboxycellulose